An empirical nexus between poverty and unemployment on economic growth - KEJI Sunday Anderu (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
The study examines the empirical nexus between poverty and unemployment on economic growth in Nigeria between 1980 and 2016. Auto-Regressive Distributed Lag (ARDL), Bound cointegration testing, and Error Correction Methods (ECM) were used to investigate the link between unemployment, poverty rate, and economic growth in Nigeria. Post estimation tests such as the Jarque-Bera test, Breusch-Pagan, ARCH test, and Ramsey reset test were also adopted in order to validate the research finding. The diagnostic tests further disclosed that the estimated model follows the Ordinary Least Square technique assumptions to attain efficiency and consistency of the model employed. The Jarque-Bera test suggests that residuals for both models are normally distributed, and the Breusch-Godfrey Serial Correlation (LM) test indicates that the hypothesis of no autocorrelation cannot be rejected. Interestingly, the ARDL and ECM results show that unemployment and poverty significantly impact economic growth both in the short and long run. Hence, the study recommended that the Nigeria government should ensure that adequate measures are put in place: Such as investment in education, agricultural sector reform, expansionary fiscal policy, intervention in micro-lending for small scale businesses by the government should be implemented to reduce the level of unemployment and poverty rate both in the short run and long run.